Analyzing the Impact of Gender Diversity and Green Accounting on Corporate Social Responsibility and Financial Performance: An Intervening Role Approach - Prasetyo, Muhamad Fahmi; Susilawati, Susi; Supriatiningsih, Supriatiningsih (IJBLE Scientific Publications Community Inc., 2025)
This research investigates the influence of gender diversity and green accounting on corporate social responsibility (CSR), with financial performance examined as a mediating variable, in energy sector firms listed in the IDX-IC index during 2019–2023. The study is motivated by the relatively low level of CSR disclosure and the suboptimal implementation of gender diversity and environmental accounting in fostering sustainability. Samples were selected using purposive sampling, and the data were analyzed through path analysis with unbalanced panel regression, supported by the Sobel test to identify potential mediation effects. The findings indicate that gender diversity and green accounting have no significant impact on financial performance. Gender diversity shows a negative influence on CSR, whereas both green accounting and financial performance demonstrate a positive and significant effect on CSR. Furthermore, economic performance is found not to mediate the relationship between gender diversity, green accounting, and CSR.